Obstacles and motivations for earthbag social housing in Chile: energy, environment, economic and codes implications - Cataldo-Born, Matías; Araya-Letelier, Gerardo; Pabón, Claudia (Revista de la Construcción. Journal of Construction, 2015)
Chile presents a social housing deficit that needs to be addressed with solutions that increase habitability and environmental benefits. This paper addresses the benefits of implementing earthbag buildings as an option to mitigate the existing social housing deficit in Chile. A literature review presents details on the use of earthbag buildings around the world, and motivations and obstacles for implementing earthbag buildings in Chile. In particular, a case study was simulated to compare an earthbag social house to a reinforced brick masonry social house in terms of environmental and economic performances such as CO2 emissions, energy and costs. It is concluded that both alternatives generate similar CO2 emissions, but the earthbag social house can save up to 20% of energy during its life cycle. In economic terms, the earthbag social house generates savings of 50% and 38% for initial investment and life cycle cost, respectively, compared to the reinforced brick masonry social house. The implementation of earthbag social housing projects would be encouraged by the development of a Chilean building code for earthbag design that provides guidance on the safe use of this technique in a seismic country.